Uwagi na temat wiersza „Don Juan i Dońa Anna” Marii Pawlikowskiej -Jasnorzewskiej - Jęcz, Jadwiga (Studia Europaea Gnesnensia, 2016)
The paper aims to offer an interpretation of “Don Juan and Dońa Anna”, a poem by Maria Pawlikowska-Jasnorzewska in the light of one of the most famed European myths. Relying on the abundant studies devoted to the oeuvre of the poet, it is also worthwhile to analyze how the poem was influenced by the social and cultural trends of its times.